2017
DOI: 10.1016/j.neuron.2017.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Amines, Astrocytes, and Arousal

Abstract: Amine neurotransmitters, such as noradrenaline, mediate arousal, attention, and reward in the CNS. New data suggest that, from flies to mammals, a major mechanism for amine transmitter action is to raise astrocyte [Ca] and release gliotransmitters that modulate neuronal activity and behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Astrocytes can release gliotransmitters including glutamate, GABA, D-serine, and ATP to influence local neurons (46,74). Phenylephrine increased glutamatergic sEPSCs onto vPAG DA neurons, this effect was preserved in the presence of TTX, and CNQX abolished phenylephrine-induced increases in sEPSCs on vPAG DA neurons (Figure 4).…”
Section: α1ars On Vpag Astrocytes Modulate Wakefulnessmentioning
confidence: 97%
“…Astrocytes can release gliotransmitters including glutamate, GABA, D-serine, and ATP to influence local neurons (46,74). Phenylephrine increased glutamatergic sEPSCs onto vPAG DA neurons, this effect was preserved in the presence of TTX, and CNQX abolished phenylephrine-induced increases in sEPSCs on vPAG DA neurons (Figure 4).…”
Section: α1ars On Vpag Astrocytes Modulate Wakefulnessmentioning
confidence: 97%
“…Additionally, the α1bAR was found in glial elements in the NAc core and shell in this study. In other brain regions, it has been shown that NE (under the control of the α1AR) from the LC could cause glutamate release from astrocytes that in turn could affect release of other neurotransmitters, such as dopamine (Mitrano et al, 2016; Bazargani & Attwell, 2017). This also points to NE-DA interactions that need further examination in the NAc, as glial contributions to neurotransmission have become of increasing interest.…”
Section: Discussionmentioning
confidence: 99%
“…Besides a2-adrenergic receptors, GIRK channels are known to be activated by mGluR2 receptors (Watanabe and Nakanishi, 2003), A1 adenosine receptors (Kim and Johnston, 2015; X. and purinergic receptors (Erb and Weisman, 2012;Filippov et al, 2004). We tested whether these signaling pathways contributed directly or indirectly (Bazargani and Attwell, 2017) to the NE-mediated GIRK activation in GoCs by bath applying the group II mGluR antagonist LY341495 (100μM; NE: 42 ± 9 pA, NE+LY: 46 ± 3 pA; n = 6; Wilcoxon signed-rank test, p = 0.688; Figure 3H) and a cocktail of the P2Y12 purinergic receptor antagonist PSB 0739 (0.1 mM; (Madry et al, 2018)) and A1 adenosine receptor antagonist DPCPX (100 nM; NE: 23 ± 5 pA, NE+PSB/DPCPX: 26 ± 3 pA; n = 7; Wilcoxon signed-rank test, p = 0.938; Figure 3I).…”
Section: Norepinephrine-mediated Hyperpolarization Is Mediated By Girmentioning
confidence: 99%
“…NE also modulates excitatory synaptic transmission onto Purkinje cells as well as down regulating the induction of synaptic plasticity (Carey and Regehr, 2009). Moreover, enhanced glial cell activity during locomotion is mediated by noradrenergic pathways (Bazargani and Attwell, 2017;Paukert et al, 2014). While noradrenergic inputs are present in all of the layers of the cerebellar cortex (Berger et al, 1979;Olson and Fuxe, 1971), noradrenergic modulation has only been reported in the molecular layer, where most plasticity is thought to occur (Gao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%